2010
DOI: 10.1590/s1983-14472010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Benefícios da utilização do brinquedo durante o cuidado de enfermagem prestado a criança hospitalizada

Abstract: RM, Favero L. Benefícios da utilização do brinquedo durante o cuidado de enfermagem prestado à criança hospitalizada. Rev Gaúcha Enferm., Porto Alegre (RS) 2010 jun;31(2):247-53. BENEFÍCIOS DA UTILIZAÇÃO DO BRINQUEDO DURANTE O CUIDADO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
54

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 10 publications
0
26
1
54
Order By: Relevance
“…Therefore, the children´s statements revealed that play can be used to recreate, stimulate, socialize and provide a ther-Rev Gaúcha Enferm. 2015 jun;36(2):76-81. apeutic function (3) . For this reason, health care professionals have the active role of recognizing the moments in which play can be used, and its purposes based on the individuality and needs of each child.…”
Section: Feel Good It´s Fun [] People Coming To Play With Me Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the children´s statements revealed that play can be used to recreate, stimulate, socialize and provide a ther-Rev Gaúcha Enferm. 2015 jun;36(2):76-81. apeutic function (3) . For this reason, health care professionals have the active role of recognizing the moments in which play can be used, and its purposes based on the individuality and needs of each child.…”
Section: Feel Good It´s Fun [] People Coming To Play With Me Wimentioning
confidence: 99%
“…Consequently, play becomes a strategy that can minimize the discomforts caused by hospitalization and assist in the fi ght against the disease. It can also facilitate nursing interventions and must be incorporated as an interface of care for children with cancer (3) . Nurses should consider play as the most appropriate way to develop empathy and as a channel to understand the world from the viewpoint of children, which subsequently encourages bonding (4) .…”
Section: Introductionmentioning
confidence: 99%
“…Essa estratégia procura mostrar aos pais a importância de sua participação ativa no processo de desenvolvimento da criança, dando-lhes suporte informativo e emocional. Estudo (19) demonstra a necessidade de melhorar a comunicação, a participação, a aceitação e a motivação da criança na atenção a sua saúde, a fim de manter a individualidade, diminuir o estresse e possibilitar a implementação de um cuidado atraumático à criança e a sua família. Ações dessa natureza remetem à necessidade de reorganização do processo de trabalho para a construção da perspectiva da integralidade do cuidado.…”
Section: Ele Fica Numa Cadeira De Rodas Que Foi O Pastor Que Deu Elunclassified
“…Aproximando o significado dos procedimentos terapêuticos ao mundo infantil, o enfermeiro favorece reaproximação da criança com sua infância, transformando a inquietação, tristeza, medo da dor e sofrimento em sinais de alegria e distração. Modificando, assim, o ambiente hospitalar, contribuindo para uma melhor recuperação da criança e diminuindo os traumas pós-hospitalização 8,17 .…”
Section: O Brincar E a Comunicaçãounclassified
“…Dentre as formas de abordagem, o brincar pode colaborar para uma melhor comunicação do profissional com a criança, ajudando na redução da ansiedade causada pela hospitalização e auxiliando no preparo do paciente pediátrico para os procedimentos. Podendo ser desenvolvido na própria enfermaria e com qualquer criança 7,8 . Os tipos de brinquedos também podem ajudar a ampliar o leque de expressões na criança.…”
Section: Introductionunclassified